2016
DOI: 10.1021/acs.jmedchem.5b01372
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Vibegron: A Potent and Selective β3 Adrenergic Receptor Agonist for the Treatment of Overactive Bladder

Abstract: The discovery of vibegron, a potent and selective human β3-AR agonist for the treatment of overactive bladder (OAB), is described. An early-generation clinical β3-AR agonist MK-0634 (3) exhibited efficacy in humans for the treatment of OAB, but development was discontinued due to unacceptable structure-based toxicity in preclinical species. Optimization of a series of second-generation pyrrolidine-derived β3-AR agonists included reducing the risk for phospholipidosis, the risk of formation of disproportionate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
87
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(92 citation statements)
references
References 52 publications
1
87
0
Order By: Relevance
“…Vibegron (MK‐4618) is a β 3 ‐adrenoceptor agonist, potently activates human β 3 ‐adrenoceptors with an EC 50 value of 1.1 nM, and vibegron is also highly selective over β 1 ‐ and β 2 ‐adrenoceptors versus β 3 ‐adrenoceptors across multiple species (Table ). Vibegron did not show any stimulating or inhibitory effects on cytochrome P450 enzymes, suggesting a low risk of drug–drug interaction (Edmondson et al, ). A recent randomized placebo‐controlled Phase III study showed that the 12‐week treatment with vibegron (50 or 100 mg once daily) resulted in a significant improvement over the placebo in changes in the mean number of micturitions per day at Week 12 from baseline (primary endpoint) and changes from baselines in OAB symptom variables (daily episodes of urgency, urgency incontinence, incontinence, and nocturia, and voided volume/micturition) as the secondary endpoints.…”
Section: Characteristics Of β3‐adrenoceptor Agonists For Oab Treatmentmentioning
confidence: 99%
“…Vibegron (MK‐4618) is a β 3 ‐adrenoceptor agonist, potently activates human β 3 ‐adrenoceptors with an EC 50 value of 1.1 nM, and vibegron is also highly selective over β 1 ‐ and β 2 ‐adrenoceptors versus β 3 ‐adrenoceptors across multiple species (Table ). Vibegron did not show any stimulating or inhibitory effects on cytochrome P450 enzymes, suggesting a low risk of drug–drug interaction (Edmondson et al, ). A recent randomized placebo‐controlled Phase III study showed that the 12‐week treatment with vibegron (50 or 100 mg once daily) resulted in a significant improvement over the placebo in changes in the mean number of micturitions per day at Week 12 from baseline (primary endpoint) and changes from baselines in OAB symptom variables (daily episodes of urgency, urgency incontinence, incontinence, and nocturia, and voided volume/micturition) as the secondary endpoints.…”
Section: Characteristics Of β3‐adrenoceptor Agonists For Oab Treatmentmentioning
confidence: 99%
“…Mirabegron, a CYP2D6 inhibitor, has been reported to have off‐target effects, whereas vibegron is metabolized independently from CYP3A4, 2D6 or 2C9, and is thus considered less likely to cause drug–drug interactions. Vibegron is also reported to be highly selective to cardiac ion channels (hERG, hCav1.2 and hNav1.5) and serotonin transporters …”
Section: Discussionmentioning
confidence: 99%
“…A β 3 ‐adrenoreceptor agonist causes smooth muscle relaxation in the bladder to increase the bladder capacity, and has attracted attention as a new therapeutic drug for OAB . Vibegron is a novel, potent and selective β 3 ‐adrenoreceptor agonist, and exerts excellent pharmacological activity ( in vitro and in vivo ) . Recently, a phase 3 study in Japanese OAB patients was carried out, and showed excellent efficacy and high tolerability of vibegron when compared with a placebo .…”
Section: Introductionmentioning
confidence: 99%
“…Vibegron is a novel, potent and selective β 3 ‐AR agonist, and possesses favorable preclinical pharmacokinetic, pharmacological and toxicological profiles in vitro and in vivo as a candidate drug for OAB . Especially regarding drug metabolism, vibegron did not show any induction and inhibitory effect on cytochrome P450 enzymes, suggesting a low risk of drug–drug interaction .…”
Section: Introductionmentioning
confidence: 99%
“…Vibegron is a novel, potent and selective β 3 ‐AR agonist, and possesses favorable preclinical pharmacokinetic, pharmacological and toxicological profiles in vitro and in vivo as a candidate drug for OAB . Especially regarding drug metabolism, vibegron did not show any induction and inhibitory effect on cytochrome P450 enzymes, suggesting a low risk of drug–drug interaction . In a phase 2b placebo‐controlled randomized clinical trial, treatments with vibegron 50 mg and 100 mg for 8 weeks in patients with OAB were generally well‐tolerated and showed improvements in OAB symptoms (NCT01314872: https://clinicaltrials.gov/ct2/show/results/NCT01314872).…”
Section: Introductionmentioning
confidence: 99%